Hydropericardium Syndrome in Broiler Chicken - M. Jeevana latha; M.K.Srikanth (The Indian Veterinary Journal, 2024)
In a poultry farm, broiler chicken aging between 3-5 weeks showed sudden onset of heavy mortality up to 20 percent. Based on specific pathognomonic lesions, the condition was confirmed as Hydropericardium disease. The present paper describes the occurrence and pathology of hydropericardium Syndrome and associated changes in broiler chicken.